Workshop Pemanfaatan Teknologi Internet of Things (IoT) menggunakan Mikrokontroler ESP32 untuk Guru-Guru SMK - Muhammad Yusro; Aodah Diamah (Bahasa Indonesia, 2022)
Abstract The rapid advancement of information technology and telecommunications has caused Internet of Things (IoT) technology to be increasingly developed and utilized in various activities and tasks at the home, office, school, industry, and others. 24-hour connectivity and various automation features make IoT an effective way to remotely monitor and manage jobs. In the context of learning in Vocational High Schools (SMK), ideally, the use of IoT technology applications is taught by teachers in the field of industrial electronics expertise. The uneven understanding and technical skills of teachers about the application of IoT technology is one of the factors that have not updated the ability of vocational students with IoT technology information. From these problems, the solution offered is to provide technical knowledge and skills to teachers about the use of IoT using a microcontroller so that they can teach it to students. The workshop/training was conducted online which was attended by 20 (twenty) teachers from several vocational schools in the Jakarta, Bekasi, Cibinong, and Bogor areas. In this workshop, theoretical and practical learning about the use of IoT technology is given. The material taught is the development of IoT, the use of the ESP32 IoT development board, and some practical examples using the ESP32 board. In this workshop, IoT learning e-modules (theory and practice) were also distributed which can be used by teachers for independent learning and as teaching materials in SMK. From the workshop, an overview of the understanding and technical skills of teachers regarding IoT technology was obtained which still needs to be improved. The participants were very enthusiastic about participating in the IoT workshop because they got new and useful information and knowledge to improve their competence in the field of industrial electronics technology. The usefulness of this workshop was felt by the participants who gave a positive impression of the material taught by the instructor/lecturer. Abstrak Pesatnya kemajuan teknologi informasi dan telekomunikasi, menyebabkan teknologi Internet of Things (IoT) makin berkembang dan dimanfaatkan dalam berbagai kegiatan dan tugas di rumah, kantor, sekolah, industri, dan lainnya. Konektivitas 24 jam serta berbagai fitur otomasi menjadikan IoT sebagai cara efektif untuk memantau dan mengelola berbagai pekerjaan dari jarak jauh. Dalam konteks pembelajaran di Sekolah Menengah Kejuruan (SMK), maka idealnya pemanfaatan aplikasi teknologi IoT diajarkan oleh para guru bidang keahlian elektronika industri. Belum meratanya pemahaman dan keterampilan teknis guru tentang aplikasi teknologi IoT, menjadi salah satu faktor belum ter-update nya kemampuan siswa SMK dengan informasi teknologi IoT. Dari permasalahan tersebut maka solusi yang ditawarkan adalah dengan memberikan pengetahuan dan keterampilan teknik kepada guru tentang pemanfaatan IoT menggunakan mikrokontroler sehingga dapat mengajarkannya kepada siswa. Workshop/pelatihan dilaksanakan secara daring yang diikuti peserta guru dari beberapa SMK di wilayah Jakarta, Bekasi, Cibinong dan Bogor sebanyak 20 (dua puluh) orang. Dalam workshop ini diberikan pembelajaran teori dan praktikum tentang pemanfaatan teknologi IoT. Materi yang diajarkan adalah perkembangan IoT, pemanfaatan ESP32 IoT development board, dan beberapa contoh praktikum menggunakan ESP32 board. Dalam workshop ini juga dibagikan e-modul pembelajaran IoT (teori dan praktik) yang dapat digunakan para guru untuk pembelajaran mandiri dan sebagai bahan ajar di SMK. Dari workshop tersebut didapatkan gambaran terkait pemahaman dan keterampilan teknis para guru tentang teknologi IoT yang masih perlu ditingkatkan. Para peserta sangat antusias mengikuti workshop IoT karena mendapatkan informasi dan pengetahuan yang baru dan berguna untuk meningkatkan kompetensinya di bidang teknologi elektronika industri. Kebermanfaatan workshop ini dirasakan sekali oleh para peserta yang memberikan kesan positif dari materi yang diajarkan oleh instruktur/narasumber.